Traditional knowledge on the universe among the Semaq Beri Tribe in Terengganu - Ramle Abdullah; Nur Hafizah Ramle; Mohd Sukhairi Mat Rasat (8(7) May 2014, Pages: 396-407, 2014)

(untitled)
Each society has its own distinctive perceptions and knowledge on the Universe, especially towards the world that has become their place of residence; such is the case of the Orang Asli, one of the indigenous communities in Malaysia. Among the Orang Asli from the Semaq Beri tribe in Terengganu State there exist a narratives or myth that describes their knowledge on such beliefs. Objective: A study by means of fieldwork was carried out towards the Semaq Beri tribe in the Kemaman district, Terengganu to obtain detailed information regarding such elements. The objectives of the study are to explore and clarify on their knowledge on natural events, the structure of the world that is home to humans and its relation to other natural elements. Data were collected using interview techniques on a number of key informants, as well as participation observation. Results: The results showed that the Semaq Beri tribe possesses a knowledge structure that is concrete towards the origin of nature’s existence and its structure. The basic form of nature in the thoughts of the Semaq Beri covers the world, the sun, moon and stars. The world is the key environmental element which possesses seven layers. Conclusion: The structural pattern of the world as presented has its own distinctive rationale and is closely related to the overall belief aspects of the Semaq Beri tribe.